Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.7718/iamure.ije.v3i1.201
|View full text |Cite
|
Sign up to set email alerts
|

Creative Learning Enrichment for Math Appreciation through Time: An Exploratory Pedagogy

Abstract: This study examined an exploratory pedagogy designed to promote mathematics appreciation through time.  It involved an infusion of some creative learning enrichment activities into the traditional approach of teaching, a process believed to heighten the interest of learners to study mathematics.  Employing a descriptive method, specifically the longitudinal approach of developmental study, and involving fifteen Electronics Engineering students from a cohesive group, the researcher probed how the unusual non-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…With the result showing the low performance of the students in Mathematics, there is a need to go back to the drawing board beginning with curriculum review, teaching strategies and understanding students' psychology towards the subject. In particular, teachers are challenged to infuse new and effective strategies like those that have been proven to provide positive results (Gregory, Gregory & Eddy, 2014;Arhin & Osei, 2013;Choi et al, 2013;Fathurrohman et al, 2013;Walkington et al, 2013;Taclay, 2013;Limjuco, 2012). Moreover, much attention must be given invested into developing a positive attitude towards the subject.…”
Section: Resultsmentioning
confidence: 99%
“…With the result showing the low performance of the students in Mathematics, there is a need to go back to the drawing board beginning with curriculum review, teaching strategies and understanding students' psychology towards the subject. In particular, teachers are challenged to infuse new and effective strategies like those that have been proven to provide positive results (Gregory, Gregory & Eddy, 2014;Arhin & Osei, 2013;Choi et al, 2013;Fathurrohman et al, 2013;Walkington et al, 2013;Taclay, 2013;Limjuco, 2012). Moreover, much attention must be given invested into developing a positive attitude towards the subject.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, students' self-efficacy in mathematics should be given attention in teaching the subject if one is serious in advancing the performance of the student. In particular, teacher educators should endeavour to infuse new and effective strategies like those that have been proven to provide positive results (Gregory, Gregory & Eddy, 2014;Arhin & Osei, 2013;Choi et al, 2013;Fathurrohman et al, 2013;Walkington et al, 2013;Taclay, 2013; Relationship between pre-service teachers' mathematics self-efficacy and their mathematics achievement C. B. Ampofo Limjuco, 2012;Asante, 2012). Since in this study self-efficacy was found to have a strong positive effect towards performance, teacher educators should make sure teacher trainees continue to develop a positive confidence themselves.…”
Section: Implication For Practicementioning
confidence: 99%